Folic Acid Supplementation Adversely Affects Chemosensitivity of Colon Cancer Cells to 5-fluorouracil. (3rd July 2016) - Ishiguro, Lisa; Yang, Michael; Sohn, Kyoung-Jin; Streutker, Catherine J.; Grin, Andrea; Croxford, Ruth; Kim, Young-In
ABSTRACT: Folic acid (FA) fortification and widespread supplemental use have significantly increased folate status in North America. Furthermore, >50% of colorectal cancer patients use FA supplement. The increased folate status may interfere with cancer chemotherapy. We investigated the effect of FA supplementation on chemosensitivity of human colon cancer cells to 5-fluorouracil (5-FU) using a xenograft model. Mice harboring human HCT116 colon cancer xenografts were randomized to receive the control, or 4× or 12.5× supplemental levels of FA. Within each diet group, mice were randomized to receive 5-FU+leucovorin or saline and xenograft growth and characteristics were determined. The expression of genes involved in folate metabolism and cancer treatment was determined. FA supplementation and 5-FU significantly interacted to influence xenograft growth ( P < 0.007). At the control level, 5-FU significantly inhibited the growth of the xenografts ( P < 0.0001). However, at the 4× supplemental level, 5-FU-treated xenografts grew faster than untreated xenografts ( P = 0.048) while at the 12.5× supplemental level, 5-FU exhibited no effect. Cell proliferation, degree of necrosis, and expression of the selected genes did not significantly differ by the supplemental levels of FA. Our data suggest that FA supplementation may be detrimental to 5-FU chemotherapy of colon cancer and pose public health concern.